Theoretical analysis and experimental study on heat transfer mechanism and thermal insulation properties of composite insulation coating. (2018) - Wei, Li; Geng, Xianfei; Du, Andong
In this paper, the theoretical analysis and experimental study were carried out on the preparation of thermal insulation coating with modified acrylic resin and high-temperature adhesive formulations as the base material, ceramic fibre as a reinforcing material and spherical hollow particles as heat insulating aggregate. The theoretical study was investigated to analyse thermal conductivity of the coating, and the experimental study was carried out to analyse the main factors affecting the performance of the insulation coating, as well as its microstructure. The simulation results show that the thermal conductivity of the coating is the sum of those of film forming binder and filler and is proportional to the thermal conductivity of the coating in a solid phase. The experimental results show the temperature of the coating outer surface can be greatly reduced and the analysis of the microstructure of the coating shows that the heat conduction can be effectively prevented.